2010
DOI: 10.1117/1.3462986
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive investigation of three-dimensional diffuse optical tomography with depth compensation algorithm

Abstract: Abstract.A depth compensation algorithm ͑DCA͒ can effectively improve the depth localization of diffuse optical tomography ͑DOT͒ by compensating the exponentially decreased sensitivity in the deep tissue. In this study, DCA is investigated based on computer simulations, tissue phantom experiments, and human brain imaging. The simulations show that DCA can largely improve the spatial resolution of DOT in addition to the depth localization, and DCA is also effective for multispectral DOT with a wide range of opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 30 publications
2
60
0
Order By: Relevance
“…Quantitative comparative studies, using both simulated and in vivo data, have demonstrated clear improvements in resolution of the tomography approach (Boas et al, 2004a;Boas et al, 2004b;Boas et al, 2001;Koch et al, 2010;White and Culver, 2010b). While elegant depth compensation algorithms have been proposed to increase the quality of depth localization of DOT (Niu et al, 2010), a full comparison of such methods is beyond the scope of the present work. The spatially-dependent regularization techniques use herein for human DOT have been detailed in references: White and Culver, 2010a, b;White et al, 2009;Zeff et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Quantitative comparative studies, using both simulated and in vivo data, have demonstrated clear improvements in resolution of the tomography approach (Boas et al, 2004a;Boas et al, 2004b;Boas et al, 2001;Koch et al, 2010;White and Culver, 2010b). While elegant depth compensation algorithms have been proposed to increase the quality of depth localization of DOT (Niu et al, 2010), a full comparison of such methods is beyond the scope of the present work. The spatially-dependent regularization techniques use herein for human DOT have been detailed in references: White and Culver, 2010a, b;White et al, 2009;Zeff et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…The detailed derivation and validation of DCA can be found in references [18,19]. The key component in DCA is the formation of a transformation matrix A # , as defined by A # = AM.…”
Section: Depth Compensation Algorithmmentioning
confidence: 99%
“…SVR has been utilized in the frequency-domain and CW-based DOT techniques for imaging human breast cancer and brain functions. Recently, we have developed a depth compensation algorithm (DCA) to significantly improve the accuracy of DOT in depth localization, as demonstrated by both laboratory phantom and human brain measurements [18,19], using fiber-based DOT systems.…”
Section: Introductionmentioning
confidence: 99%
“…One such important task in DOT is the detection of absorptive heterogeneous regions, which we refer to as the signal, within the tissue. In DOT, often the anomalous regions are distinguished by a higher absorption coefficient compared to the rest of the tissue [17][18][19][20][21][22]. However, the sensitivity of diffuse-light measurements drops off quickly with penetration depth due to the high scattering in the tissue, which leads to poor depth resolution in DOT [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Metrics such as contrast-to-noise ratio (CNR) and positional errors (PE) [17,18,24,28] have been used to evaluate the performance of depth resolution provided by DOT reconstruction algorithms. The PE metric quantifies the error in locating a signal, while the CNR gives a measure of the whether the object can be detected from the background.…”
Section: Introductionmentioning
confidence: 99%